Responsabilização Pós-Consumo e Logística Reversa:: O Caso das Embalagens de Agrotóxicos no Brasil - Cometti, José Luís Said; Alves, Isabel Teresa Gama (Sustainability in Debate, 2010)
The pesticides packages bring risk of human and environmental contamination. This paper presents an analysis from the perspective of sustainability, system of collection and disposal of pesticides packages in Brazil, created from the Law 9974/2000, which established liability for after consumption packaging. In 2002 was created the National Institute of Packaging Processing (Inpev) that uses the principle of Reverse Logistics, aiming to return the packages to the business cycle by recycling. It was found that the system has contributed to the reduction of environmental impacts and requires amendments to sustainability.